Beyond addiction: a phenomenological study of former smokers' experiences in cessation - Maulidya, Rusda; Isni, Khoiriyah; Trisnowati, Heni; Jatmika, Septian Emma Dwi; Santri, Ichtiarini Nurulita; Tukiyo, Intan Wahyuni (Universitas Ahmad Dahlan, 2025)
Although daily smoking appears to be declining, quitting remains difficult, and relapses are common. Cessation support often emphasizes strengthening quit intentions and motivation while replacing smoking with meaningful daily activities (e.g., work or prayer). This qualitative phenomenological study explored the experiences of former smokers, interviewing four primary informants (ex-smokers) and four supporting informants involved in their quit attempts. Social influences and work demand shaped cessation efforts. Graphic depictions of smoking-related illnesses and messages about harm to children were salient motivators. A community “healthy, smoke-free home” initiative existed at the study site, designated as a pilot area, but was largely unknown and implemented without involvement from health personnel. All informants reported at least one relapse. These findings suggest that promoting smoke-free homes as a community-empowerment strategy, coupled with visible risk communication and stronger engagement of health workers, may increase awareness and better support sustained cessation.